Students’ Perceptions Toward the Use of Digital Reading Platforms for Improving Reading Comprehension in EFL Classrooms - Dinda; Nurdin Noni; Munir (International Journal of Language, Education, and Literature, 2025)
eleventh-grade students at SMKS YPPP Wonomulyo during the 2024/2025 academic year. In addition, it sought to examine students' perceptions regarding the effectiveness of digital reading platforms in supporting the development of their comprehension abilities. A quantitative research method was adopted, utilizing a quasi-experimental design to assess the impact of the intervention. The population consisted of second-grade students majoring in Computer and Network Technology, drawn from five available classes. Using a cluster random sampling technique, two classes were selected, one designated as the experimental group and the other as the control group, with each consisting of 32 students. The experimental group received instruction using the ReadWorks platform, while the control group continued with conventional reading materials.Data were collected through a Likert-scale questionnaire comprising 10 items that measured students’ perceptions and experiences related to the use of ReadWorks. The results indicated that students exhibited a generally positive attitude toward the digital platform, with an overall mean score of 42.7, indicating a very positive perception. Most respondents emphasized the benefits of multimedia features, notably the vocabulary support tools and audio functionalities, which aided in their understanding of more complex texts. Students reported that these features made reading activities more engaging, accessible, and less intimidating, ultimately improving their comprehension outcomes. These results suggest that the use of technology-enhanced reading platforms should be encouraged as a means of supporting students' academic success in reading Keywords: Digital Reading Platforms, ReadWorks, Reading Comprehension, Students’ Perceptions, EFL Classroom.